Prosedur Pelaksanaan Mutual Legal Assistance terhadap Pemulihan Aset Hasil Korupsi yang Dilarikan ke Luar Negeri - Ricardo Santos (Jurnal Hukum Lex Generalis, 2021)
The purpose of this study is to find out how the procedures for implementing Reciprocal Assistance in Criminal Matters as well as to find out what can hinder the recovery process of assets resessed abroad is reviewed from Law No. 1 of 2006 on Reciprocal Assistance in Criminal Matters. The research method used is the normative legal research method. Legal resources used are from legislation and secondary legal materials as well as interviews with relevant law enforcement. Based on the results of the study found several essential things that affect the success and rapidly slow recovery process of criminal assets abroad such as case handling and evidentiary process, the flow of application for assistance, the response of the country requested assistance and other factors.